3D Design Platform of Virtual National Costume Based on Digital Nonlinear Random Matrix. (30th July 2022) - Zhang, Mingyan; Shen, Luolan
Abstract : The traditional two-dimensional clothing CAD system is more and more difficult to meet the needs of the three-dimensional design of virtual national clothing products. Based on the digital nonlinear random matrix theory, this paper constructs a three-dimensional design platform for virtual ethnic clothing and proposes a weighted graph tree representation method for the deviation transfer process of nonlinear ethnic clothing. The model first analyzes the business links and information related to the deviation transfer modeling of ethnic clothing and establishes a hierarchical relationship tree, a method of expressing the order of ethnic clothing, and a method of expressing deviation. The weighted graph tree model and construction rules of the deviation transmission process realize the integrated expression of the deviation transmission information of ethnic clothing and solve the nonlinear problem in the transmission of ethnic clothing deviation. During the simulation process, the article uses the three-dimensional geometric modeling tool POSER to establish a standard entry model, edit it in 3DS MAX and export the file, read it, and parameterize it through programming, and realize the drawing of the three-dimensional avatar model based on OpenGL. The experimental results show that the parametric avatar model established by the system is accurate and realistic and can quickly convert the 3D style to the N-dimensional pattern.